State and Farmers’ Protest in India - Valarthodi, Mohamed Iyas; Ekayanta, Fredick Broven (Jurnal Kajian Agraria dan Kedaulatan Pangan (JKAKP), 2024)
The Indian farmers' protests against the government's agricultural reforms marked a pivotal moment in the country's history, resonating not only nationally but also garnering international scrutiny and support. The Marxist theory of the state, which holds that the state primarily serves as an instrument of class power, advancing the interests of the ruling capitalist class at the expense of the working class, is used to study the farmers' response to the creation farmers' bills in India. This article employs the study of documents containing secondary data from the journal, news, working paper, and official website. The analysis highlights that the government has consistently favored capitalist interests, contributing to the marginalization of these farmers, and the current laws are seen as a continuation of this trend, further entrenching the power of large agribusinesses. The farmers, therefore, represent a significant moment of struggle against neoliberal policies that prioritize corporate interests ahead of the demands of the agrarian community.